PANINI PROJECTION EFFECT AS MEANS OF REDUCING PERSPECTIVE DISTORTIONS - P. A. Kachanov; A. A. Zuev; K. N. Yatsenko (Системный анализ и прикладная информатика)
The method based on Panini projection to reduce perspective distortions of images with wide viewing angle is considered. The analysis of the features of construction of Panini projection is provided. A realization of the effect on the graphic accelerators as a result of post-processing is proposed. The results of using the described effect in computer graphics were obtained. A comparison of images in the perspective projection and Panini projection was carried out. It is shown that perspective projection of a three-dimensional scene onto the surface of a parabolic cylinder reduces distortions.